(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Investors in India’s capital market have access to a wide variety of venture alternatives, which enables them to participate in a diverse array of entrepreneurial endeavors while still realizing a financial return on their investments. When compared to other types of financial instruments, mutual funds are regarded by industry professionals as offering the lowest level of risk in conjunction with the best possible returns. Because mutual fund schemes have become one of the most responsive investment routes in India’s capital market, enormous speculative growth has occurred as a direct consequence of this development. Investors are actively urged to engage in speculative activity as a direct effect of the existence of asset management businesses. At this time, there are a total of 44 asset management companies (AMCs) operating in the mutual fund industry. Because of this one particular condition, it is necessary to keep a careful eye on and evaluate mutual funds. Recently, there has been a tremendous increase in the number of sales of mutual funds. As part of this examination, the roles that the public sector and the private sector play in advantage management organizations will both be investigated. When conducting our investigation into the methodical application of a variety of mutual fund strategies, we will make use of factual criteria such as beta, standard deviation, Treynor’s measure, and the Sharpe ratio. The findings of this research will lead to better informed decisions being made about investments as a consequence..